Augmentation of EPR Effect and Efficacy of Anticancer Nanomedicine by Carbon Monoxide Generating Agents - Fang, Jun; Islam, Rayhanul; Islam, Waliul; Yin, Hongzhuan; Subr, Vladimir; Etrych, Tomas; Ulbrich, Karel; Maeda, Hiroshi (Pharmaceutics, 2019)
One obstacle to the successful delivery of nanodrugs into solid tumors is the heterogeneity of an enhanced permeability and retention (EPR) effect as a result of occluded or embolized tumor blood vessels. Therefore, the augmentation of the EPR effect is critical for satisfactory anticancer nanomedicine. In this study, we focused on one vascular mediator involved in the EPR effect, carbon monoxide (CO), and utilized two CO generating agents, one is an extrinsic CO donor (SMA/CORM2 micelle) and another is an inducer of endogenous CO generation via heme oxygenase-1 (HO-1) induction that is carried out using pegylated hemin. Both agents generated CO selectively in solid tumors, which resulted in an enhanced EPR effect and a two- to three-folds increased tumor accumulation of nanodrugs. An increase in drug accumulation in the normal tissue did not occur with the treatment of CO generators. In vivo imaging also clearly indicated a more intensified fluorescence of macromolecular nanoprobe in solid tumors when combined with these CO generators. Consequently, the combination of CO generators with anticancer nanodrugs resulted in an increased anticancer effect in the different transplanted solid tumor models. These findings strongly warrant the potential application of these CO generators as EPR enhancers in order to enhance tumor detection and therapy using nanodrugs.